Cultivar and insecticide spraying regimes effects on insect pests and grain yield of cowpea in the dry savannas of north-eastern Nigeria - Kamara, A.Y.; Chikoye, David; Omoigui, L.O.; Dugje, I.Y. (African Crop Science Society, 2007)
Cowpea is an important food legume and versatile crop in the savannas of northeast Nigeria. Despite the high potential for production in this region, insect pests are a major constraint. A study was conducted to evaluate the response of diverse cowpea genotypes to different schedules of spraying with an insecticide. The study revealed that flower thrips the legume pod borer, (Maruca), and a range of pod sucking bugs were the major insect pests. Application of insecticides increased grain yield by 75-126% depending on the frequency of spraying. Improved cultivars recorded a higher grain yield than the local checks at all spraying regimes. The cultivar IT98K-131-2 recorded higher grain yield when no insecticide was applied suggesting that this cultivar was either tolerant or resistant to the insect pests.